Komatiitic nickel troughs: inverted rift systems - Gordon, R. (TRABAJOS DE GEOLOGÍA, 2009)
Embayments of ultramafic rocks into their underlying substrate, commonly referred to as troughs, host the majority of Kambalda style komatiitic nickel deposits. Various different models have attempted to explain these troughs through post-mineralization tectonism, syn-volcanic rifting, thermal erosion of the substrate or pre-eruptive topographic effects. Within the McLeay and Long orebodies, structures bounding these troughs and smaller scale structures within them, contain conflicting shear sense indicators and have highly variable fault offsets indicating episodes of both normal and reverse displacement. These structures separate zones of markedly different volumes of primary volcanic sulphide accumulation at the basal ultramafic contact and in some parts of the orebody host a far greater volume of sulphide than the surrounding basal contact. These relationships indicate the existence of the structures during primary sulphide accumulation. Independence Group’s Long Nickel Mine provides outcrop-scale evidence for trough formation through syn-volcanic rifting and later inversion of the rift structures. This explanation for trough formation is a synthesis of existing models, which have predominantly been justified with large-scale geometrical analyses of entire orebodies.